2014
DOI: 10.2147/amep.s63435
|View full text |Cite
|
Sign up to set email alerts
|

How valid are commercially available medical simulators?

Abstract: BackgroundSince simulators offer important advantages, they are increasingly used in medical education and medical skills training that require physical actions. A wide variety of simulators have become commercially available. It is of high importance that evidence is provided that training on these simulators can actually improve clinical performance on live patients. Therefore, the aim of this review is to determine the availability of different types of simulators and the evidence of their validation, to of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 133 publications
0
27
0
2
Order By: Relevance
“…If this occurs, especially early in a training sequence, there is either a problem with the simulator task (i.e., the task does not produce adequate performance data that allow discriminating between levels of expertise, which is a problem that needs to be fixed), or the trainee is not a true novice. No more than four cases (1)(2)(3)(4) need to be considered for generating clear performance feedback any novice can understand and take into account to attain an optimal speed-precision trade-off.…”
Section: Towards Expert-based Speed-precision Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…If this occurs, especially early in a training sequence, there is either a problem with the simulator task (i.e., the task does not produce adequate performance data that allow discriminating between levels of expertise, which is a problem that needs to be fixed), or the trainee is not a true novice. No more than four cases (1)(2)(3)(4) need to be considered for generating clear performance feedback any novice can understand and take into account to attain an optimal speed-precision trade-off.…”
Section: Towards Expert-based Speed-precision Controlmentioning
confidence: 99%
“…Finally, whatever the simulator, a single performance metric inevitably gives a partial assessment of user performance [20]. Task completion time as a sole criterion has been explicitly demonstrated to be a poor or even misleading measure of surgical skill [1,23]. Some metrics assume a simple global optimum value, such as a minimal tool path length, or a minimal completion time, and other quantities such as forces [6,21] or velocities [23,[33][34][35].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a recent study has shown that even when these systems are available at the teaching hospitals, they are underused because they are physically locked away, perhaps owing to their cost (Brennan, Loan, Hughes, Hennessey, & Partridge, 2014). The second issue is related to the lack of validity of measurements used to assess the surgical performance on these systems (Stefanidis & Heniford, 2009; Thijssen & Schijven, 2010; Våpenstad & Buzink, 2013; Stunt, Wulms, Kerkhoffs, Dankelman, van Dijk, & Tuijthof, 2014). This is perhaps due to the novelty of these systems and suggests that additional research is needed to validate these measurements.…”
Section: Related Workmentioning
confidence: 99%
“…Advances in this field have prompted a rapid expansion in the number of commercially marketed surgical simulators, with more than 400 models currently available. 16 As surgical procedures can be deconstructed into a series of steps in which a learner can be trained and assessed, many simulators focus on the particular surgical skills involved in one of these steps, enabling deliberate practice of important and common aspects of procedures. These skills can be practiced efficiently until competency is acquired without exposing patients to undue risk.…”
mentioning
confidence: 99%